2010
DOI: 10.1258/shorts.2010.010007
|View full text |Cite
|
Sign up to set email alerts
|

The World Health Organization's ‘Surgical Safety Checklist’: should evidence-based initiatives be enforced in hospital policy?

Abstract: ObjectivesTo assess the awareness and voluntary usage of the World Health Organization's Surgical Safety Checklist (WHO SSC), just prior to its mandatory implementation.DesignQuestionnaire-based, prospective, telephone survey.SettingPatients are exposed to systematic risks and principles of surgical safety are inconsistently applied even in sophisticated settings. The evidence-based WHO SSC addresses shortfalls to promote patient safety. It was formally introduced in the United Kingdom in January 2009 and beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 7 publications
(7 reference statements)
0
31
0
Order By: Relevance
“…One investigation found that items were confirmed more commonly during time‐out (range 100–72 per cent) than during sign‐out (range 86–19 per cent), but only 13 per cent of time‐outs and 3 per cent of sign‐outs were checked properly (all items validated). Sivathasan and co‐workers asked 421 hospitals in the UK, before the national roll‐out, about use of the surgical safety checklist and found that it was compulsory in 65 per cent. They argued that much greater education and awareness would be needed for the roll‐out to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…One investigation found that items were confirmed more commonly during time‐out (range 100–72 per cent) than during sign‐out (range 86–19 per cent), but only 13 per cent of time‐outs and 3 per cent of sign‐outs were checked properly (all items validated). Sivathasan and co‐workers asked 421 hospitals in the UK, before the national roll‐out, about use of the surgical safety checklist and found that it was compulsory in 65 per cent. They argued that much greater education and awareness would be needed for the roll‐out to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Compliance with SC use has been shown to be generally good overall, but some studies have suggested some SCs or their components are ‘often neglected’, or skipped . Studies assessing implementation of SCs at a national level are uncommon, although Nugent et al.…”
Section: Introductionmentioning
confidence: 99%
“…1,[7][8][9][10] Compliance with SC use has been shown to be generally good overall, 6,12 but some studies have suggested some SCs or their components are 'often neglected', or skipped. 12,13,14 Studies assessing implementation of SCs at a national level are uncommon, although Nugent et al identified compliance gaps and implementation barriers in a survey of Irish hospitals. 15 In Australia, the use of SCs has been supported by professional organizations, State Governments and the Australian Commission on Safety and Quality in Healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Where the SSC was not compulsory, 80 % were using it informally or sporadically. One-quarter of senior theater personnel in hospitals without compulsory use indicated that they did not know or that their department did not plan on using the checklist in the next 6 months, despite a deadline for implementation [23].…”
Section: Safety and Surgerymentioning
confidence: 99%